The Immunomodulatory Potential of Hesperidin from Garut Orange Peel (Citrus nobilis var. chrysocarpha) Against Human Metapneumovirus (HMPV) Infection: Based on In Vivo Mouse Model Study - sugiah, sugiah; Dadang Muhammad Hasyim, Dadang Muhammad Hasyim; Marsha Yulianti, Marsha Yulianti; Akbar Nurjamil, Akbar Nurjamil; N. Ai Erlinawati, N. Ai Erlinawati (Karsa Husada Health Institute Garut, 2025)
Acute respiratory infections (ARIs), including those caused by Human Metapneumovirus (HMPV), remain a global health concern, and no specific therapy or vaccine is currently available. Hesperidin, the main flavonoid in Garut orange peel (Citrus nobilis var. chrysocarpha), is known for its anti-inflammatory, antiviral, and immunomodulatory activities. This study was an in vivo pilot study using 35 male Balb/c mice divided into seven groups: normal control, negative control (5% imiquimod), positive control (levamisole), and hesperidin-treated groups at 50, 100, and 150 mg/kg body weight, either alone or in combination with imiquimod. Observed parameters included total leukocytes, lymphocytes, neutrophil-to-lymphocyte ratio (NLR), body weight, organ weight, and lung histology. Hesperidin was extracted using 70% ethanol and identified by thin-layer chromatography (TLC).Results showed that body weight data were normally distributed, with no significant differences between groups (p > 0.05), indicating that hesperidin was safe at the tested doses. Hematological analysis revealed significant differences in leukocyte counts (p = 0.001), lymphocytes (p = 0.002), and NLR (p = 0.001). Imiquimod induced systemic inflammation, as evidenced by increased leukocytes, lymphocytes, NLR, and lung inflammation scores. Hesperidin exhibited dose-dependent immunomodulatory effects; the 100 mg/kgBW dose combined with imiquimod produced the most optimal results, characterized by low NLR and a histology score of 0, reflecting controlled inflammation and effective adaptive immune activation. In contrast, the 150 mg/kgBW dose triggered excessive inflammatory responses.